Analisis Perencanaan Strategis Penyelesaian Konflik Papua - Charizatul Janna Asdi Putri; Bambang Wahyudi; Anang Puji Utama; Pujo Widodo; Herlina JR Saragih (CV. AFDIFAL MAJU BERKAH, 2025)
The conflict in Papua is a complex issue rooted in historical, political, social, and cultural factors. Papua has been Indonesia since 1969, but tensions persist due to separatist movements, the Free Papua Movement (OPM), and dissatisfaction with the region’s development and resource management. This research aims to analyze strategic planning in conflict resolution, focusing on governmental policies and their implementation. The study adopts a qualitative approach, using in-depth interviews, observation, and a literature review. In-depth interviews were conducted with informants from local communities, experts, and academics to gain comprehensive insights into the conflict’s dynamics. Observations were made to better understand social interactions and conflict resolution mechanisms, while the literature review helped frame theoretical perspectives on conflict resolution. The research finds that despite the implementation of the Special Autonomy Law (Otsus) in 2001, challenges such as lack of transparency in fund allocation and weak institutional roles, like the Papuan People's Assembly (MRP), persist. As a solution, the study suggests strengthening Special Autonomy by facilitating dialogue among all stakeholders, including neutral international mediators. It also recommends improved strategic planning in policy development, emphasizing the principles of equality, honesty, openness, and sincerity in the dialogue process to achieve effective and sustainable conflict resolution.